1992
DOI: 10.1111/j.1399-302x.1992.tb00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic peroral immunization of conventional laboratory rats with mutans streptococci leads to stable acquired suppression of salivary antibodies

Abstract: Prior investigations have demonstrated that salivary antibody responses to mutans streptococci are dose-dependent and temporary. The purpose of this study was to evaluate the stability of antibody suppression established by mutans streptococci. Streptococcus mutans 6715-15 was provided in food to conventional rats for 18 weeks. Antigen was withdrawn for 10 weeks and then resumed for an additional 6 weeks. Saliva and serum from nonimmunized controls and from experimental rats were tested with a quantitative enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…In the present study, whole bacterial cells were used as antigens, and consequently the ELISA readings may have been the result of antibody reactions with many different antigens. It is possi-Age-related saliva antibodies 61 ble that antibodies to irrelevant antigens may dominate those reacting with antigens involved in colonization and pathogenesis and salivary antibody responses to whole cells may have differed from those when measured against extracted antigens (23). On the other hand, the use of purified antigens may not represent relevant pathogenic mechanisms (5).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, whole bacterial cells were used as antigens, and consequently the ELISA readings may have been the result of antibody reactions with many different antigens. It is possi-Age-related saliva antibodies 61 ble that antibodies to irrelevant antigens may dominate those reacting with antigens involved in colonization and pathogenesis and salivary antibody responses to whole cells may have differed from those when measured against extracted antigens (23). On the other hand, the use of purified antigens may not represent relevant pathogenic mechanisms (5).…”
Section: Discussionmentioning
confidence: 99%
“…As stated earlier, there is evidence that the host is more tolerant to autochthonous than allochthonous bacteria (115,281). The chronic exposure of the host immune system to resident bacteria may result in the suppression of the antibody response (391,392,433). Riviere et al (391,392) demonstrated that primary oral immunization with S. mutans may induce SIgA antibodies in rats but that continued exposure to S. mutans whole cells led to progressive suppression of the SIgA response and the level of salivary IgA antibodies returned to baseline (391,392).…”
Section: Active Immunization Against Oral Diseasesmentioning
confidence: 92%
“…Most studies on inducing salivary IgA against mutans streptococci to confer protection against dental caries have been performed in rodents ( Table 7). Different antigen preparations were used for immunization and include whole cells (245,321,331,333,341,392,479), cell walls (331,332), glucosyltransferase (448-450, 480, 482), surface proteins (100,214,382,409,516,534), ribosomal preparations (172), synthetic peptides In general, immunization with whole cells gives rise only to salivary IgA antibodies while immunization with soluble antigens and adjuvant, which render the antigens particulate, may also lead to an increase in the level of antibodies in serum. (260), and anti-idiotypic antibodies (207).…”
Section: Active Immunization Against Oral Diseasesmentioning
confidence: 99%
See 2 more Smart Citations